Bisphenol A disrupts steroidogenesis and induces a sex hormone imbalance through c-Jun phosphorylation in Leydig cells. (October 2017) - Lan, Hsin-Chieh; Wu, Kai-Yu; Lin, I-Wen; Yang, Zhi-Jie; Chang, Ai-An; Hu, Meng-Chun
Abstract: Bisphenol A (BPA) is a well-known endocrine disrupting chemical (EDC) that is used to manufacture plastic consumer products. It is well known that exposure to BPA can induce defects in gonad development and negatively influences reproductive function in both males and females. In this study, we assessed the effects of BPA on hormone production in Leydig cells, which secrete hormones in the testes and support male fertility. We examined two steroidogenic enzymes, CYP11A1 and CYP19 that involved in sex hormone synthesis in mouse MA-10 Leydig cells. We found that BPA activated CYP gene in both mRNA and protein levels then resulted in alteration of the normal sex hormone ratio. Furthermore, we found that BPA induced c-Jun phosphorylation and contributed to CYP gene expression. Similar results were observed in an animal study. In conclusion, BPA disrupts the hormone environment in testis via steroidogenic gene activation through the JNK/c-Jun signaling pathway. Graphical abstract: Highlights: BPA increases the risk of estrogen hypersecretion in testis. BPA stimulates aromatase and triggers sex hormone imbalance through JNK signaling. BPA changes the hormone profile at non-cytotoxic dose.